Chest Pain Patients at Veterans Hospitals Are Increasingly More Likely to Be Observed Than Admitted for Short Stays - Brad Wright PhD; Amy M. J. O'Shea PhD; Justin M. Glasgow MD, PhD; Padmaja Ayyagari PhD; Mary Vaughan Sarrazin PhD (SAGE Publishing, 2016)
Observation stays are an outpatient service used to diagnose and treat patients for extended periods of time while a decision is made regarding inpatient admission or discharge. Although the use of observation stays is increasing, little is known about which patients are observed and which are admitted for similar periods of time as inpatients. The aim was to identify patient characteristics associated with being observed rather than admitted for a short stay (<48 hours) within the Veterans Health Administration (VHA). In our longitudinal analysis, we used logistic regression within a generalized estimating equation framework to model observation stays as a function of patient characteristics, time trends, and hospital fixed effects. To minimize heterogeneity between groups, we limit our sample to patients with a presenting diagnosis of chest pain. Our analysis includes a total of 121 584 hospital events, which consist of all observation and short-stay admissions for chest pain patients at VHA hospitals between 2005 and 2013. Both the absolute and relative use of observation stays increased markedly over time. The odds of an observation stay were higher among women, but lower among older patients and rural residents. Despite strong evidence that chest pain patients are increasingly more likely to be observed than admitted, suggesting a substitution effect, we find little evidence of within-hospital disparities in VHA observation stay use.